Dynamic simulation of the target moderator cryoplant and cryogenic transfer line at the European Spallation Source. Issue 1 (1st May 2022) - Chao, Y; Weisend, J G; Arnold, P; Gan, Z
Abstract: Large scale helium cryoplant is an important sub-system in large science facilities. Dynamic simulation by computer is proved to be an effective method to design and optimize large scale helium cryoplant. This study builds a dynamic simulation model for the Target Moderator Cryoplant and the cryogenic transfer line in European Spallation Source using Dymola and Modelon library. This cryoplant can provide 30.3 kW cooling power at 15 K. The main parts of the system including the screw compressor, turbine, heat exchanger, warm gas buffer and gas management panel are simulated. The model is verified by the acceptance data. Dynamic simulation is carried out to study the cooling down process and transient heat load scenarios. The influence of the cryogenic transfer line to the cryoplant is analysed according to simulation results. This simulation could predict the response of the cryoplant to transient heat load and benefit the steady operation of the cryoplant.